Prevalence of multimorbidity among Bangladeshi adult population: A nationwide cross-sectional study - Khan, Nusrat; Rahman, Mahfuzar; Mitra, Dipak; Afsana, Kaosar (BMJ Journals, 2022)
This article was published in BMJ Open [ © Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2019-030886. The Journal's website is at: https://bmjopen.bmj.com/content/9/11/e030886